The Natural History of Spinocerebellar Ataxia Type 3 in Mainland China: A 2-Year Cohort Study - Peng, Yun; Peng, Linliu; Chen, Zhao; Peng, Huirong; Wang, Puzhi; Zhang, Youming; Li, Yangping; Wang, Chunrong; Shi, Yuting; Hou, Xuan; Long, Zhe; Yuan, Hongyu; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: The natural history of spinocerebellar ataxia type 3 (SCA3) has been reported in several populations, and show heterogeneity in progression rate and affecting factors. However, it remains unexplored in the population in mainland China. This study is aimed to identify the disease progression rate and its potential affecting factors in patients with SCA3 in mainland China. Participants and Methods: We enrolled patients with genetically confirmed SCA3 in mainland China. Patients were seen at three visits-baseline, 1 year, and 2 years. The primary outcome was the Scale for the Assessment and Rating of Ataxia (SARA), and the secondary outcomes were the Inventory of Non-Ataxia Signs (INAS) as well as the SCA Functional Index (SCAFI). Results: Between October 1, 2015, and September 30, 2016, we enrolled 263 patients with SCA3. We analyzed 247 patients with at least one follow-up visit. The annual progression rate on SARA was 1.49 points per year (SE 0.08, 95% confidence interval [CI] 1.33-1.65, p < 0.0001). Annual progression of INAS and SCAFI were 0.56 points per year (SE 0.05, 95%CI 0.47-0.66, p < 0.001) and -0.30 points per year (SE 0.01, 95% CI -0.33 -0.28, p < 0.001), respectively. Faster progression in SARA was associated with longer length of expanded allele of ATXN3 (p < 0.0001); faster progression in INAS was associated with lower INAS at baseline (p < 0.0001); faster decline in SCAFI was associated with shorter length of normal allele of ATXN3 (p = 0.036) and higher SCAFI at baseline (p < 0.0001). Conclusion: Our results provide quantitative data on the disease progression of patients with SCA3 in mainland China and corresponding affecting factors, which could facilitate the sample size calculation and patient stratification in the future clinical trials.